Investigating The Helfer Skin Tap Technique's Effectiveness in Reducing Pain During Intramuscular Injections in Children Below Five Years - Navreet Kaur Bains; Dr. Charan Singh (International Journal of Scientific Research in Science and Technology, 2024)
Intramuscular injections are a common and necessary medical procedure for neonates, required for vaccinations and medication administration. However, these injections can cause significant pain and distress, not only causing immediate discomfort but potentially leading to longer-term consequences in infant development and behaviour. The traditional approach to managing this pain often relies on pharmacological interventions, which can have their own risks and side effects. As a result, there is growing interest in non-pharmacological methods that are safe, effective, and can be easily implemented in clinical settings. The Helfer Skin Tap Technique, grounded in the Gate Control Theory of pain, presents a promising alternative. This theory posits that non-painful inputs, such as tapping or stroking the skin, can interfere with pain signals traveling to the brain, thus reducing the perception of pain. By providing a simple distraction from the painful stimulus, the technique potentially offers a practical method of pain reduction without the complications associated with drugs. Despite the potential benefits, research into the Helfer Skin Tap Technique's effectiveness in neonates during intramuscular injections remains limited. Current studies have shown mixed results, with some indicating significant reductions in pain perception and others showing minimal impact. This variability underscores the need for further research to establish standardized protocols and confirm the technique’s efficacy across different settings and populations. This study aims to fill the gap in current research by systematically evaluating the Helfer Skin Tap Technique in a controlled, clinical environment with a focus on neonates. By measuring pain responses through validated tools like the Premature Infant Pain Profile (PIPP) and comparing outcomes between intervention and control groups, this research seeks to provide definitive evidence on the technique's utility, paving the way for more humane and effective pain management strategies in neonatal care.
Keywords: Intramuscular Injections; Pain Perception; Infant Pain; Humane; Intervention; Neonates